Quantifying adiabatic motion in the outer radiation belt and ring current with invariant matching - da Silva, D. E.; Elkington, S. R.; Li, X.; Hudson, M. K. (Frontiers in Astronomy and Space Sciences, 2024)
Adiabatic motion is a fundamental reversible process for geomagnetically trapped particle populations, including particles comprising the ring current and radiation belts. During adiabatic motion, a particle's trajectory in configuration space responds to sufficiently slow changes in the magnetospheric magnetic field. Previous research has highlighted expected patterns in adiabatic motion, such as radial motion or the D st effect. In this work, we introduce a method we call Invariant Matching for quantifying adiabatic motion between a pair of magnetospheres. This method can be applied to both simulation and semi-empirical magnetic field models, is computationally efficient, and in particular does not require tracing the particle trajectories. In this work, we use the the Tsyganenko and Sitnov 2005 (TS05) magnetic field model, and present adiabatic motion between a storm commencement, the time of the storm's D st minimum, and a nominal recovery time. We also analyze adiabatic motion which occurs in response to enhancements of individual major current systems (including the ring current, Chapman-Ferraro current, Birkeland current, and tail current). Our methodology yields vector fields quantifying the displacement of mirror points throughout the magnetosphere, prepared in a way appropriate for application to both outer radiation belt and ring current populations.